TINJAUAN TERHADAP PENJUALAN KOSMETIK ILEGAL/TANPA IZIN BERDASARKAN UNDANG-UNDANG NOMOR 8 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS: PUTUSAN NOMOR 186/PID.SUS /2018/PN PTI) - Anju Syafana Ananda; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
Thoughts of the Panel of Judges in viewing and selecting cases in the crime of illegal/unlicensed demonstration of selling makeup in Choice Number 186/Pid.Sus/2018/PN.Pti, especially from a juridical and non-juridical perspective. The juridical perspective is the thought of the Panel of Judges, which considers the position, indictment and request of the examiner, witnesses, evidence and facts in the preliminary interaction. Meanwhile, the non-juridical reflection by the Panel of Judges included the basis of the plaintiff's activities, the results of the respondent's activities, the social and monetary conditions of the plaintiff and the strict components of the plaintiff. It was these two reflections that decided the Panel of Judges to select/enchant the plaintiffs. Thoughts of the Panel of Judges in viewing and selecting cases in the crime of selling makeup illegally/without permission in Choice Number 186/Pid.Sus/2018/PN.Pti, especially from a juridical and non-juridical perspective. The juridical perspective is the thought of the Panel of Judges, which considers the position, indictment and request of the examiner, witnesses, evidence and facts in the preliminary interaction. Meanwhile, the non-juridical reflection by the Panel of Judges included the basis of the plaintiff's activities, the results of the respondent's activities, the social and monetary conditions of the plaintiff and the strict components of the plaintiff. It was these two reflections that decided the Panel of Judges to choose/enchant the plaintiffs.